Churchill [videorecording (DVD)] - Cox, Brian, 1946-; Richardson, Miranda; Slattery, John, 1962- (Cohen Media Group, 2017)
June 1944. Allied Forces stand on the brink: a massive army is secretly assembled on the south coast of Britain, poised to re-take Nazi-occupied Europe. One man stands in their way: Winston Churchill. An impulsive, sometimes bullying personality; fearful, obsessive and hurting. Fearful of repeating, on his disastrous command, the mass slaughter of 1915, when hundreds of thousands of young men were cut down on the beaches of Gallipoli. Obsessed with fulfilling historical greatness: his destiny.